Psicomotricidad: prácticas y conceptos - BOTTI, Pablo comp. (MIÑO Y DAVILA, 2003)
Contiene: AGNESE, Lucila; ARNAIZ SANCHEZ, Pilar; BANDERAS, Lilian; BERRUEZO Y ADELANTADO, Pablo; CALMEIS, Daniel; DABAS, Elina; DE ARETIO, Mónica; MILA, Juan; PAPAGNA, Silvia; RAVERA, Claudia; SASSANO, Miguel; SCHEINES, Graciela; VAN GELDEREN, Alfredo